The New humanities reader - Miller, Richard E. (Richard Earl) 1961-; Spellmeyer, Kurt (Wadsworth Cengage Learning, 2012)
Presents 25 challenging and important essays from diverse fields that address current global issues. This cross-disciplinary anthology helps readers attain the analytical skills necessary to become informed citizens. Ideas and research from wide-ranging sources provide opportunities for students to synthesize materials and formulate their own ideas and solutions. The thought-provoking selections engage students and encourage students to make connections for themselves as they think, read, and write about the events that are likely to shape their lives. The Fourth Edition includes nearly 25percent new selections, which continue to make this text current, globally oriented, interdisciplinary, and probing. -- Description from http://www.booktopia.com.au (Mayb 20, 2015).